Effects of linear modes on the evolution of discrete solitons - Peschel, Ulf; Lederer, Falk; Morandotti, Roberto; Eisenberg, Hagai S.; Silberberg, Yaron; Aitchison, J. Stewart (J. Opt. Soc. Am. B, JOSAB, 2006)
We investigate, theoretically and experimentally, how linear modes evolve around discrete solitons. If the shape of the exciting beam is not matched to a soliton state, linear modes are excited, resulting in significant oscillations of the beam amplitude. Linear modes can cause a power increase in a single guide, where the effect of nonlinear absorption is enhanced tremendously. As a result we observe a splitting of the soliton, which is highly asymmetric in case of a tilted input beam. In the latter case most of the emerging field distribution finally moves opposite to the initial tilt.
Publisher: Optica Publishing Group
Keywords: High power lasers; Laser sources; Nonlinear absorption; Nonlinear effects; Optical fields; Photonic crystals